THU0490 Multicentre study of lupus nephritis urinary biomarkers in adult and paediatric patients. (15th June 2017) - Reis, P Costa; Maurer, K; Schanberg, L; Burnham, JM; Scheven, E von; O'Neil, K; Gitelman, M Klein; Petri, M; Sullivan, KE
Abstract : Background: Glomerulonephritis is an important cause of morbidity and mortality in patients with systemic lupus erythematosus, particularly in children. Presently, renal histology is used for the diagnosis of lupus nephritis (LN), but it only offers a description of a confined area of the kidney and is seldom repeated for monitoring due to its invasiveness. Urinary biomarkers that reflect LN activity and have prognostic value are much needed to guide the judicious use of immunosuppressive drugs in these patients. We focused on three potential LN biomarkers: HER2, TWEAK and VCAM1. HER2 (Human Epidermal Growth Factor Receptor 2) controls cell proliferation by regulating the intracellular levels of miR-26a and miR-30b, which inhibit the expression of cell-cycle related genes. HER2 was recently shown to be dramatically overexpressed in the kidneys of LN patients and in NZM2410 mice. TWEAK (TNF-related weak inducer of apoptosis) is involved in pro-inflammatory responses, angiogenesis and fibrosis. TWEAK is increased in the kidneys of LN patients. VCAM1 (vascular cell adhesion molecule 1) participates in the acute phase of inflammation, controlling leukocyte infiltration. Urinary VCAM1 has emerged as a reliable indicator of the LN activity index. Objectives: To determine the clinical value of urinary HER2, TWEAK and VCAM1 as biomarkers of LN activity. Methods: A multicentre study is being performed in an adult and paediatric cohort. All patients have biopsy-proven LN. Clinical data and urine samples are being collected in each visit. Controls are age and sex matched individuals without renal disease. Flares are identified with the SELENA-SLEDAI flare index. Urine supernatants are analysed by commercial enzyme-immunoassays for HER2, TWEAK and VCAM1. Results: Currently, we have studied 83 LN paediatric patients and 38 controls. The majority are female (85%). The average age is 15±2.5 years. This cohort includes Hispanic (36%), Asian (29%), African-American (21%) and Caucasian (11%) children. LN class III or IV was diagnosed in 67% of patients. Nearly all were treated with hydroxychloroquine and steroids (95%). Other drugs used include mycophenolate mofetil (85%), cyclophosphamide (43%), rituximab (27%) and tacrolimus (2%). A significant increase in urinary HER2, TWEAK and VCAM1 levels was found in LN patients (p=0.005; p=0.006; p=0.01, respectively) when compared to controls. HER2 levels reflected disease activity, increasing during flares. In an adult cohort of LN patients (N=126) composed mainly of females (80%) with an average age of 46±13 years, we also found a significant increase of urinary HER2 when compared to controls (p=0.002). A strong correlation between the urinary levels of HER2, TWEAK and VCAM1 was not found. Conclusions: Urinary HER2, TWEAK and VCAM1 were significantly increased in a paediatric cohort of LN patients. In addition, significantly higher urinary HER2 levels were also found in an adult LN cohort. This on-going study will further evaluate if these urinary markers, alone or in combination, can reflect disease activity and predict renal flares, analysing their potential value in clinical practice. References: PMIDs: 26016809; 22727560; 22788914. Disclosure of Interest: None declared